2021
DOI: 10.1021/acs.inorgchem.1c03236
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the OER Kinetics of the Less-Explored α-MnO2 via Nickel Doping Approaches in Alkaline Medium

Abstract: Development of a low-cost transition metal-based catalyst for water splitting is of prime importance for generating green hydrogen on an industrial scale. Recently, various transition metal-based oxides, hydroxides, sulfides, and other chalcogenidebased materials have been synthesized for developing a suitable anode material for the oxygen evolution reaction (OER). Among the various transition metal-based catalysts, their oxides have received much consideration for OER, especially in lower pH condition, and Mn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…[16] Bera, Krishnendu et al constructed Ni-doped MnO 2 by a simple wet chemical synthesis route and its OER performance was significantly improved. [17] Zhao and his co-workers fabricated Ag-doped CoSe 2 materials through a simple cation exchange method and exhibited a significant improvement in the OER activity when utilized as OER electrocatalysts. [18] Ali Saad et al [19] reported borophene decorated with Ag nanoparticles as a support, which showed greatly enhanced OER performance for Co 3 O 4 catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Bera, Krishnendu et al constructed Ni-doped MnO 2 by a simple wet chemical synthesis route and its OER performance was significantly improved. [17] Zhao and his co-workers fabricated Ag-doped CoSe 2 materials through a simple cation exchange method and exhibited a significant improvement in the OER activity when utilized as OER electrocatalysts. [18] Ali Saad et al [19] reported borophene decorated with Ag nanoparticles as a support, which showed greatly enhanced OER performance for Co 3 O 4 catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…After Ni doping, the positions of Mn 2p peaks have no obvious change, which can be seen in Figure c. However, the Mn 3+ /Mn 4+ ratio in NMO/CC (1.38) was higher than that in MnO 2 /CC (1.35), which may be attributed to the Ni 2+ doping that causes the reduction of Mn cations from Mn 4+ to Mn 3+ . Mn 3+ cations were considered to have positive effects on OER performance .…”
Section: Resultsmentioning
confidence: 96%
“…The wavelength between 500 and 700 cm –1 was considered as the characteristic area of MnO 2 . Accordingly, the peak at ∼576 cm –1 is attributed to the stretching vibrations of O-Mn-O bonds in [MnO 6 ] groups, and the Raman peak at ∼634 cm –1 corresponds with the stretching vibrations of Mn–O bonds between the [MnO 6 ] sheets. , A decrease in intensity ratio between 576 and 634 cm –1 ( I 576 / I 634 ) can be observed, which implies the insertion of Ni in the tunnels of MnO 2 crystals. In addition, a slight negative shift of the Raman peak at ∼576 cm –1 can be observed in the inset image of Figure b, which can be associated with the decreased force constant of stretching vibrations of Mn–O bonds. Due to the insertion of Ni cations, electrons tend to transfer from Ni sites to Mn 4+ sites, further weakening the Mn–O bonds and decreasing the force constant of the corresponding bonds. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quick global population growth and numerous consumptions of fossil fuel energy have led to severe environmental pollution and energy crisis; thus, the development of sustainable renewable energies has aroused extensive attention in order to alleviate these phenomena. Based on the efficient utilization of hydrogen and oxygen, proton exchange membrane fuel cells (PEMFCs) have been deemed as one of the most promising new energy devices with the high energy conversion, low working temperature, fast start, and environmental sustainability. The sluggish catalytic kinetic of the oxygen reduction reaction (ORR) occurs in the cathode of PEMFCs, which limits the efficiency and application of the large-scale practical applications. At present, platinum (Pt)-based catalysts are widely acknowledged as the first choice for ORR. However, the scarcity and high cost of Pt also hamper the further widespread implementation for PEMFC applications. Moreover, the working condition of PEMFCs, including high potential and strong acidity, exerts great influence on durability of electrocatalysts .…”
Section: Introductionmentioning
confidence: 99%